2017
DOI: 10.1097/shk.0000000000000806
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Microrna Expression in Blood Leukocytes from Patients with the Acute Respiratory Distress Syndrome

Abstract: Background MicroRNA (miRNA) control gene transcription by binding to and repressing the translation of messenger RNA (mRNA). Their role in the acute respiratory distress syndrome (ARDS) is undefined. Methods Blood leukocytes from 51 patients enrolled in a prior randomized trial of corticosteroids for ARDS were analyzed. After screening eight patients with microarrays for altered miRNA expression, 25 miRNAs were selected for further analysis using RT-PCR in all 51 patients. Results On day 0, the 51 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Potential age-dependent differences in the host response at a later time point could exist and may also explain outcome differences. Studies have suggested that a prolonged inflammatory response is associated with an adverse outcome [50, 51]. Moreover, there is evidence of age-dependent temporal differences in the host response in critically ill patients (e.g., a hyper-inflammatory response during the later phase of disease and a prolonged inflammation in elderly) [17, 20, 5256].…”
Section: Discussionmentioning
confidence: 99%
“…Potential age-dependent differences in the host response at a later time point could exist and may also explain outcome differences. Studies have suggested that a prolonged inflammatory response is associated with an adverse outcome [50, 51]. Moreover, there is evidence of age-dependent temporal differences in the host response in critically ill patients (e.g., a hyper-inflammatory response during the later phase of disease and a prolonged inflammation in elderly) [17, 20, 5256].…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone positively influenced the lung functions and attenuated inflammation (Mokra et al 2007, Kosutova et al 2016. There is also increasing evidence that lower dose of GC administered earlier after developing ARDS could be beneficial (Meduri et al 2007, Narute et al 2017, Yang et al 2017. However, due to heterogeneous nature of ARDS the appropriate dosing regimens, timing and duration of GC therapy as well as reasonability for their use are still discussed.…”
Section: Vol 68mentioning
confidence: 99%
“…miRNA have shown to regulate genes involved in normal lung physiology and inflammatory lung states [ 114 ]. A recent paper studied miRNA present in blood leukocytes of patients with ARDS during the first week of care, with a particular focus on the effects of corticosteroid therapy on miRNA expression during the first week of care [ 115 ]. The authors identified 21 miRNA that are expressed at increased levels at the onset of ARDS, remain elevated at day 3 and increase further by day 7, suggesting that the underlying inflammatory processes that led to ARDS remained active at day 3 and the enhanced miRNA expression by day 7 may have a role in the resolution of inflammation.…”
Section: Treatmentsmentioning
confidence: 99%